2019
DOI: 10.1093/bib/bbz046
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive overview of oncogenic pathways in human cancer

Abstract: Alterations of biological pathways can lead to oncogenesis. An overview of these oncogenic pathways would be highly valuable for researchers to reveal the pathogenic mechanism and develop novel therapeutic approaches for cancers. Here, we reviewed approximately 8500 literatures and documented experimentally validated cancer-pathway associations as benchmarking data set. This data resource includes 4709 manually curated relationships between 1557 paths and 49 cancers with 2427 upstream regulators in 7 species. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 36 publications
0
24
0
3
Order By: Relevance
“…More complex annotation records express a combination of multiple attributes. For example, each of the annotations from the Cancer Pathway Association Database20 (CPAD) contain seven attributes to describe a relationship between a protein or miRNA, a pathway and their effect on a specific cancer type (SupplementaryFigure S4). The pathway and gene sets are also part of the annotation database, as these are useful for functional characterization of omics data and enrichment analysis.Overall, the annotations database included 5,475,532 records about 20,365 proteins, virtually the whole protein-coding genome, 19,566 complexes and 182 miRNAs.…”
mentioning
confidence: 99%
“…More complex annotation records express a combination of multiple attributes. For example, each of the annotations from the Cancer Pathway Association Database20 (CPAD) contain seven attributes to describe a relationship between a protein or miRNA, a pathway and their effect on a specific cancer type (SupplementaryFigure S4). The pathway and gene sets are also part of the annotation database, as these are useful for functional characterization of omics data and enrichment analysis.Overall, the annotations database included 5,475,532 records about 20,365 proteins, virtually the whole protein-coding genome, 19,566 complexes and 182 miRNAs.…”
mentioning
confidence: 99%
“…More complex annotation records express a combination of multiple attributes. For example, each of the annotations from the Cancer Pathway Association Database (CPAD) (Li et al, 2020) contain seven attributes to describe a relationship between a protein or miRNA, a pathway, and their effect on a specific cancer type (Fig EV3). The pathway and gene sets are also part of the annotation database, as these are useful for functional characterization of omics data and enrichment analysis.…”
Section: Resultsmentioning
confidence: 99%
“…7). Furthermore, we focused on the roles of pathways related to more than 25% anticancer drug responses in tumorigenesis and found that some of them were experimentally validated to be associated with many cancer types according to a reliable database CPAD [53]. Especially, some notable oncogenic pathways are consistently implicated in most cancers, for example, AMPK signaling pathway, p53 signaling pathway, Jak-STAT signaling pathway and MAPK signaling pathway.…”
Section: Resultsmentioning
confidence: 99%